Formatting an experiential learning education module to encourage dysphagia assessment in apheresis patients. Issue 1 (2nd August 2017) - West, James; Stutzman, Sonja E.; Atem, Folefac; Olson, DaiWai M.
Abstract: Background: Dysphagia screening is oftentimes a focus of hospitalized patients, but dysphagia can also occur in outpatient settings. Dysphagia can be overlooked by nurses and clinicians, and it is therefore important to educate nurses on the importance of dysphagia screenings. Methods: This was a randomized prospective pilot study to compare the effect of experiential learning versus traditional PowerPoint learning regarding nurses' attitudes towards performing dysphagia screening in an outpatient setting. Twelve pre and post‐test surveys were collected from nurses working in outpatient apheresis about their attitudes towards dysphagia screening. Additionally, 128 electronic medical records (EMR) were reviewed to determine if education increased the occurrence of dysphagia screening. Results: There was a statistically significant difference in the pre vs. post‐test group scores ( P  < .001), but due to small sample size, there was insufficient evidence to reject the null hypothesis that nurses had changed their attitudes towards dysphagia screening. Comparing documentation of dysphagia assessment in the EMR, there was not a significant difference in practice before or after the educational intervention ( P  = 0.18). Conclusions: The study results showed that the both types of teaching strategies are possible with nurses and they were receptive to both. Although the results of this study did not show a significant difference in practice, more research is needed to determine how to raise awareness and put this into practice.